THE TECHNOLOGY OF INTERNAL THREAD CUTTING OF HIGH PRECISION IN PARTS OF SHIP MACHINE COMPONENTS, MACHINERY AND SHIP ARMATURE - N. M. Vagabov; A. Z. Kurbanov; M. A. Magomedova (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Conducted laboratory studies of the threading in the details of ship machinery and ship armatures from hard materials helped to create the modern technology of internal threads of small diameters cutting. The reasons that impede the processing of hard materials are find out.Presented are various designs of taps for cutting of internal threads and analyzed is their work. Noted are shortcomings of their designs resulting in creating a modern cutting pattern, allowing to minimize the shortages identified in the processing of hard materials. Practice shows that the machining of these materials is difficult because of their considerable tendency to work hardening during deformation, high viscosity, poor heat dissipation from the cutting zone.They have a low coefficient of thermal conductivity and low coefficient of workability relatively to tool steel. Therefore, processing technology and cutting conditions used for structural carbon steels, often are unacceptable to hard materials.The most difficult is tapping into the holes of small diameters up to 16 mm. The disadvantage of this technology is the low quality of threaded surfaces and an increased tendency to tap breakage. To improve threading performance in the details of the hard materials are developed advanced threading techniques.